Zagrożenie bezpieczeństwa militarnego Rzeczypospolitej Polskiej przez Związek Radziecki w okresie międzywojennym - Włodarkiewicz, Wojciech (Przegląd Wschodnioeuropejski, 2022)
The article elucidates the endangerment to Poland's military security by the USSR in the interwar period of three sub-periods: 1921-1926, 1926-1935, and 1935-1939. The fragmentary sources of the undertaken research complexity are dispersed, secured in the Polish and foreign archives. In Poland, the reconnoiter of this topic began after the turn of 1989. Almost throughout the entire period under investigation, the Polish supreme State and military authorities assessed that the USSR (until December 30th, 1922, Russia) is the biggest threat to Poland's military security. In March 1939, they reconsidered this assessment focusing on Germany as the main threat to Poland's independence, mistakenly assuming that in the early period of the war, the USSR would remain neutral. The article analyzes, therefore, the Polish assessments of the USSR's sinister actions aimed at undermining the security of the Republic of Poland, and Polish counteractive decisions and safeguarding activities